Finite Element Analysis of External Toothed Plate of Internal Translation Reducer - Han Xiaojuan; Hu Xianfeng; Guo Hui; Dou Linrui (Jixie chuandong)
The outer gear ring plate is the key part of the translation in gear reducer drive,its strength is directly related to dynamic performance of the machine. In view of the new type of translation within three axial symmetry type three-ring gear reducer,its basic structure and transmission principle are analyzed,and combining the static moment equilibrium conditions and the deformation coordination equation,the tooth plate bearing load is analyzed. For 10 different working condition of external gear plate finite element static analysis and modal analysis,in order to further explore the translational reducer provides the theory basis for extensive practicability. The results show that the external tooth plate bearing load is smooth,no dead point operation,and the tooth plate stress strength meet the requirements. The resonance region is avoided,can work normally.